Putting the cycle back into business cycle analysis - Beaudry, Paul; Galizia, Dana; Portier, Franck (American Economic Review)
Are business cycles mainly a response to persistent exogenous shocks, or do they instead reflect a strong endogenous mechanism which produces recurrent boom-bust phenomena? In this paper we present evidence in favor of the second interpretation and we highlight the set of key elements that influence our answer. The elements that tend to favor this type of interpretation of business cycles are (i) slightly extending the frequency window one associates with business cycle phenomena, (ii) allowing for strategic complementarities across agents that arise due to financial frictions, and (iii) allowing for a locally unstable steady state in estimation. - Reproduced
Keywords: Investment, Capital, Intangible Capital, Capacity